Understanding the Cognitive Processes involved in Technological Entrepreneurial Opportunity Recognition - Reddy, P. Bhaskara; Reddy, R. Praven; Madhu, S. (Transactions on Engineering and Computing Sciences, 2015)
In the state-of-the art An Agenda for Future Research, Corbett and McMullen (2011) summarize the current state of the research in the following words - “Despite its many achievements, learning at the connection of free enterprise and cognition has focused primarily on the consequences of what happens when an industrialist profit from various cognitive characteristics, resources, or other dispositions. As such, cognitive study in free enterprise continues to experience from narrow theoretical articulations and weak theoretical practicalities that lower its role to the managerial sciences.”According to Santos and Eisenhardt (2004)“ entrepreneurs categorize innovative opportunities for the conception of worth, and construct a market around those opportunities” triumphant chance appreciation leads to successful start-ups and leads to the vibrancy of economy. However, very little work has been done in this field (Mitchell et al., 2014).